Non-formal Education Management at the Community Learning Center (CLC) Jakarta (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This study examines the management of non-formal education in CLC Jakarta. The purpose of this study is to analyze the planning, implementation, supervision and evaluation, leadership, and management information systems. This study uses a qualitative approach with a descriptive research type, data collection techniques using observation interviews and documentation. Informants from the head of CLC, curriculum deputy, staff, 3 tutors, and 3 students. Data analysis techniques used in this study include data collection, data reduction, data presentation, and drawing conclusions. This shows that CLC in Jakarta has managed non-formal education effectively, and is oriented towards improving the quality and sustainability of the institution. The study is expected to provide a clear picture of non-formal education management in CLC and provide recommendations for managers to improve CLC.